The advantages of humanistic science learning tools - Sudarto Sudarto (International Journal of Trends in Mathematics Education Research, 2022)
This study aimed to determine the advantages of humanistic science learning tools. The collection data was cocducted by in-depth interviews and questionnaire. Data analysis techniques used namely: data reduction, data display, and  conclusions drawing. The results of this study showed that the advantages of humanistic science learning tools were (1) making the teachers  could teach Science easily, (2) providing high  motivations to the teachers in teaching Science, (3) making the teachers more aware in developing the students' emotional, spiritual, and creativity potentials in Science learning, (4) Making the students felt happy to the Science learning, (5) Making the students  more easier to understand the Science, (6) Motivating the students to learn Science, (7) Making the students more aware  that the  emotional, spiritual, and creativity potential had to be grown in science learning and (8) Opening students' horizons to develop their emotional, spiritual, and creative potential in their daily lives independently.